The digitalisation of future work and employment: Possible impact and policy responses - Chris Warhurst; Wil Hunt (European Commission, Joint Research Centre (JRC), 2019)
This Working Paper outlines claims about the "future of work" (as the shorthand for work and employment) and the policy responses to those claims. It is based on a review of the academic and grey literatures on digitalisation and the future of work. The paper first explains the two main developments by which the new digital technologies are shaping work and employment - Industrie 4.0 and Uberisation, and the claims of the death of work and the death of employment arising respectively from these developments. It then examines the policy responses to each development, finding responses to the first to be centred on welfare rights and the second to be centred on labour rights. It also examines past and newly emerging empirical evidence about the future of work, including other trends that are impacting this future. The review suggests that digital technology will not deterministically shape the future of work but that options and choices exist over what and how technology is implemented and with what effects. It concludes by offering a number of policy pointers about how the future of work and its understanding can be better developed.
Keywords: 330; digitalisation; future of work; labour rights; technological determinism; welfare rights